Stockhausen 35: Oberlippentanz - Ave - Tierkreis (Trio- version) - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1993)
OBERLIPPENTANZ / UPPER-LIP-DANCE for piccolo trumpet, 4 horns and 2 percussionistsAVE for basset-horn and alto fluteTIERKREIS / ZODIAC Trio Versionfor clarinet, flute and piccolo flute, trumpet and piano.......